Think Pair Share and Google Classroom in Teaching English for Young Learners: A Literature Review - Irmawati, Monica Ratna; Wahyuni, Sri (Language Circle: Journal of Language and Literature, 2025)
This research paper examines the evolution of English language education in Indonesian elementary schools, particularly the transition from the 2013 Curriculum to the Merdeka Curriculum, and connects this shift to the current educational emphasis on deep learning. The Merdeka Curriculum promotes greater flexibility, student-centered learning, and competency-based assessment — all of which align with the principles of deep learning, which prioritizes critical thinking, creativity, and the meaningful application of knowledge rather than rote memorization. The paper highlights the need for effective English instruction for young learners, underscoring the significance of the critical period for language acquisition in children aged 2–13 and advocating for tailored teaching methodologies that address their unique characteristics. It emphasizes the challenges of teaching English to young learners compared to adults and proposes cooperative learning strategies, specifically the Think-Pair-Share technique, integrated with digital tools such as Google Classroom, to foster engagement, collaboration, and higher-order thinking skills. Using a literature review methodology, the study reviewed 25 peer-reviewed articles and reports published between 2015 and 2024, selected based on their relevance to English language teaching for young learners, cooperative learning strategies, technology integration, and the Indonesian or comparable contexts. The synthesis of these studies demonstrates that innovative teaching methods aligned with deep learning principles can improve language skills, participation, and teamwork among elementary students. Ultimately, the research offers actionable insights, including recommendations for integrating collaborative learning techniques and educational technology to advance deep learning and effective English instruction in Indonesian elementary schools.